Prognostic Factors in Sepsis.: Statistical Analysis of 100 Cases - Correa Rivero, Humberto; Bagnulo, Homero; Bagattini, Juan C (Cirugía del Uruguay, 1981)
A study of the statistical significance as prognostic factors of severa! clinical and laboratory findings comprised 100 septic patients interned in the Intensive Care Unit of the Hospital de Clínicas (University Medica! School Hospital) of Montevideo.